Um olhar sobre a própria prática com modelagem matemática na educação matemática ao estar-com-um-grupo de formação continuada - Santos, Lucimara Aparecida (2019)
Researches about Mathematical Modeling in Mathematical Education has been expanding, and most of them show interest in teacher’s training in Mathematical Education. We realize that there is still a lack of research on the ways teachers perform the practice with Mathematical Modeling in classroom. In our literature review we found investigations that focused on studying groups of teachers in a continuing education environment in Mathematical Modeling. However, we did not find investigations conducted by teachers about there own practice with Mathematical Modeling in a Mathematical Modeling formation group context. In order to contribute to researches regarding teachers training in Mathematical Modeling we took part in the Continuing Education Group for Teachers in Mathematical Modeling in Mathematical Education. Our investigation is guided by the interrogation: How being-with-the-group influences on my practice? While dealing with it, we seek to make explicit the movements of the formation that had not yet been thematized within the formation group itself. Assuming a phenomenological stance of qualitative approach to carry out the investigation, we turn our attention to the importance of the formation group for the movement of changing practice of the teacher/researcher. The materials collected in the form of audio recordings and written texts made by the teacher/researcher about the meetings with the formation group and about the practices implemented in the classroom constituted the research data. In the meetings with the formation group we were aware of the moments of theoretical studies, elaboration and implementation of Modeling practices by the teachers of the training group and the discussions about the practices implemented by the teacher/researcher. In classroom, we focused on the implementations of Modeling practices in an intentional movement of a practice’s change. At first, the data were transcribed to highlight the units of meaning that were convergent to our questioned phenomenon. We used the qualitative analysis software Atlas.ti to highlight the meaning units. Afterwards, the units of meaning were organized on a spreadsheet in five open categories. That are: 1) How to accept and incorporate Modeling in its practice; 2) How to see yourself as a teacher with or without Modeling; 3) How to elaborate; choose and plan the practice with Modeling; 4) How to proceed with Modeling; 5) How to see Modeling. The interpretations of the open categories showed, among other things, a movement of change in the pedagogical practice of the teacher inserted in a Mathematical Modeling formation group. Belonging to the formation group provided the opportunity for the teacher/researcher to approach Mathematical Modeling in its theoretical and practical aspects. The teacher’s understanding about the Modeling work in classroom revealed that it is permeated by obstacles to be overcome gradually. The experiences shared with the teachers belonging to the formation group served as a reference so that the teacher/researcher could reflect about her methods to be a teacher with Modeling and or without it, establishing new perspectives to her professional formation.